Recovery rate, debt structure and valuation within U.S. bankruptcy law - Wang, Xiyang (2017)
The U.S. Bankruptcy Code is a frequently used channel to resolve corporate financial distress. In the code, liquidation (Chapter 7) and reorganization (Chapter 11) are two most crucial processes. My PhD thesis discusses several important issues around the U.S. Bankruptcy Code, including recovery rate determination in bankruptcy, debt valuation in bankruptcy under a two-class debt structure and determination of an optimal bankruptcy threshold. With the aim of linking corporate finance and asset pricing, new models of credit risk are developed in this thesis and fruitful empirical implications are generated.